2021
DOI: 10.47391/jpma.2020-774
|View full text |Cite
|
Sign up to set email alerts
|

A survey of violence and vulgarity in children television programs: a content analysis, and assessment of perceptions of parents and children (ViCTiM study)

Abstract: Objectives: To quantify the depiction of violence and vulgarity in television programmes for children, and to assess the perception and practices of parents and children about television programmes meant for children. Methods:  We conducted this mixed-methods cross-sectional study in Karachi, Pakistan in the months of August-September 2018, after approval from the ethics review board of Dow University of Health Sciences, Karachi. First, a content analysis of over 102 hours of various television programmes mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…In 2021, the number of studies significantly increased to n=9 [19]- [27]. The number of studies remained consistent in 2022 with n=9 [28]- [36], and in 2023 with n=9 studies [37]- [45] respectively. The increase in the number of studies from 2019 to 2023 indicates that research on children's screen time continued to be a priority.…”
Section: Distribution Of Past Studiesmentioning
confidence: 70%
See 4 more Smart Citations
“…In 2021, the number of studies significantly increased to n=9 [19]- [27]. The number of studies remained consistent in 2022 with n=9 [28]- [36], and in 2023 with n=9 studies [37]- [45] respectively. The increase in the number of studies from 2019 to 2023 indicates that research on children's screen time continued to be a priority.…”
Section: Distribution Of Past Studiesmentioning
confidence: 70%
“…India follows this with n=5 studies [15], [17], [29], [36], [41]. There are n=3 studies found in Pakistan [24], [26], [28] suggesting a growing awareness of the importance of understanding children's screen time in the country. Four countries -Germany [19], [22], Malaysia [30], [44], Ireland [21], [34] and United Kingdom [12], [27] share a similar number of studies with n=2.…”
Section: Distribution Of Past Studiesmentioning
confidence: 90%
See 3 more Smart Citations